CNSC-03. NEURONAL INTERMEDIATE FILAMENT (NIF) ANTIBODY POSITIVE PARANEOPLASTIC SYNDROME IN A PATIENT WITH METASTATIC NEUROENDOCRINE PANCREATIC CARCINOMA AND TREATMENT WITH IPILIMUMAB/NIVOLUMAB. (14th November 2022) - Rodriguez, Karla Mora; Peguero, Edwin; Pina, Yolanda; Strosberg, Jonathan; Verma, Neha; Mokhtari, Sepideh
Abstract: Immune checkpoint inhibitors, such as ipilimumab (CTL-4) and nivolumab (PD-1) have shown effectiveness in many types of neoplasia. This combination has been used as salvage immunotherapy for high grade metastatic pancreatic carcinoma. Nevertheless, severe neurologic immune-mediated adverse effects can result from the use of this treatment. We present a case of a 64-year-old woman with metastatic neuroendocrine pancreatic carcinoma with abrupt left facial and oculomotor cranial nerve palsy as well spastic tetraplegia after one dose of ipilimumab/nivolumab. She had a history of sudden onset diplopia, fever and ground-level fall a few hours after her initial dose of immunotherapy. Initial laboratory assessment showed pronounced lymphocyte predominant leukocytosis and mild chronic hyponatremia. In the following hours, she developed right mydriasis, right sided fast phase nystagmus and right central facial paralysis along with weakness and spasticity in four extremities. Neuroimaging of brain, orbits and CTL spine showed enhancement of intra-orbital and intracranial optic nerves as well chiasm, linear enhancement from C4-C7 and cauda equina, as well as abnormal signal along thoracic spinal cord and conus medullaris. Routine EEG demonstrated non-etiology specific encephalopathy. Lumbar puncture had normal opening pressure, mild pleocytosis, hyper-proteinorrhachia and normal glucose. Viral panel and cytology in the CSF were negative, and myeline basic protein was elevated. She was treated with high dose steroids which improved overall strength and CN palsies. Twenty days after initial presentation, she suddenly developed hypotension, tachypnea, and altered cognition. The patient and family opted for comfort measures only. She passed away that same day. Late report of CSF antibody panels showed positive cell-based assay for heavy and light chain NIF with a titer of 1:512. This case emphasizes the importance of recognition of anti-body mediated paraneoplastic syndromes in patients treated with immunotherapy, their appropriate treatment and prognosis.